Marriage Intentions Among Cohabiters in Lithuania - Dirsytė, Irma (Socialinė teorija, empirija, politika ir praktika, 2021)
Living together in one household without being married in modern society is one of the defining features characterizing the transformations of the modern family, mentioned alongside late-age marriage, late-age childbearing, or frequent divorces. Marriage is still a major life transformation, but the pressure to marry today is lighter than ever before and many young couples in Europe start family life from living together in one household and not being married. However, cohabitation has not a universal meaning and role in family formation process and couples cohabit for different reasons and motives. Existing research proves, that union formation pattern depends on socioeconomical and sociodemographic characteristics, it varies by country and changes by time.In the research literature, cohabitation diffusion process is mainly based on the two arguments: cultural value changes which leads to “less marriage” and economic restrains which leads to postponed marriage until economic stability.The aim of this article is to investigate the intentions of cohabitors to marry and the factors modelling these intentions in Lithuania. The empirical analysis is based on the current Family and Inequality Survey (2019) data set about 1970-1984 birth cohort who lived in an extramarital partnership at the time of the research. The data consists rich information on the partnership and fertility, but also social and economic standing. Analysis of the data shows that, most of the cohabiting individuals in the analyzed cohort in Lithuania still undecided about marriage and could not name their intentions in the future. Descriptive statistics suggests that more man than women plan to marry their partner in the future. In addition, cohabitors with the lowest education level do not intend to marry their partner more than any another education level group.The multinomial regression results suggest that factors predicting marriage in the future are sex, partnership satisfaction and education. That leads to assume that in Lithuania cohabitation is only a prelude to marriage and individuals satisfied with the quality of their relationship intends to marry rather than continuing cohabitation as an alternative to marriage. Cohabitation can be chosen as a prelude to marriage to check the strength of a relationship and to accumulate economic and social resources. On another hand, having one child has a negative effect on the marriage intentions among cohabitors.
Keywords: cohabitation; marriage; cohabitators intentions to marry